Vestibular failure managed with osteopathic manipulative treatment: A report of two cases. Issue 3 (July 2020) - Origo, D.; Tarantino, A.G.; Romagnoli, M.
Abstract: Introduction: Vestibular failure or hypofunction can be generated by pathologies such as vestibular neuritis (VN), causing the onset of rotatory vertigo and the vestibulo-ocular reflex (VOR) hyporeaction. VN is a post-viral inflammation-producing vestibular nerve-axon impairment, which reaches compensation in 70% of cases. Here, we present two cases of vestibular failure that did not respond to pharmacological therapy, but did show modulated vestibular response after an osteopathic manipulative treatment. Dizziness handicap inventory (DHI) was used to assess disability, while VOR was examined by means of video head impulse test (v-HIT). Case 1 showed bilateral VOR areflexia with severe related disability due to chronic vertigo, while case 2 showed sub-acute VN complicated by intense vomiting. After treatment, both cases had a complete remission of symptoms, with a reduction in DHI score of 60 and 70 points respectively, as well as a normalization of the v-HIT exam. Conclusion: OMT might work to modulate VOR, through osteopathic manipulation of the fascial-system and interaction with proprioceptive inputs. Further clinical trials should be performed to investigate the OMT clinical efficacy in uncompensated vestibular neuritis.